ANALISIS NILAI TAMBAH ABON SAPI PADA INDUSTRI RUMAH TANGGA “SRI REJEKI” DI KOTA PALU - Laweangi, Fleiss Amelia; Muis, Abdul; Baksh, Rukavina (AGROTEKBIS, 2018)
This study aims to determine the added value derived from crude meat processed into beef floss industry Sri Rejeki households in the city of Palu. The location determination was done intentionally (purposive). Respondents in this study are the leaders and employees of Sri Rejeki domestic industry in the city of Palu. Data were obtained from the primary data and secondary data. The analysis used is the analysis of the value added by Hayami method. The results showed that (1) Income Beef floss in household industries Sri Rejeki IDR. 5,780,384 / kg; (2) Value-added Beef floss in household industries Sri RejekiIDR. 69,843.75 / kg with a ratio of 41.57% what were indicated domestic industry Sri Rejeki in managing the beef floss provide added value that is classified so as to obtain benefit.